Spider fauna associated with wheat crops and adjacent habitats in Buenos Aires, Argentina - Armendano, Andrea Viviana (2011)
A census of spiders was undertaken in winter wheat fields of Buenos Aires province, Argentina, as well as from their margins and from wheat stubble. Spiders were collected weekly over 3 consecutive years using entomological sweeping and pitfall traps. Field margins were the richest and densest habitats (H’= 3.27, J’= 0.82) and registered 52 species from 14 families, while 31 species from 13 families were found in wheat. Thomisidae and Araneidae were the most abundant families in the herbaceous layer of both the margins and the crop, and Lycosidae in the soil litter. In contrast, 17 species from 8 families were recorded from wheat stubble, making it the least diverse habitat surveyed (H’= 1.67, J’= 0.72). These results could be related to repeated disturbance of wheat fields by harvest, tillage and other field work. Furthermore, the similarity observed in the families of both margin and crop communities indicates that colonization of wheat fields is from the adjacent areas.